Beyond 12 Angry Men: Thin-Slicing Film to Illustrate Group Dynamics. (August 2013) - Waller, Mary J.; Sohrab, Golchehreh; Ma, Bernard W.
The ability of group members to shape group behaviors can greatly influence collective outcomes; however, the skills associated with correctly recognizing behaviors in situ and responding appropriately to them on a real-time basis are typically not emphasized in group dynamics education. In this article, we describe a pedagogical method that uses film excerpts and a thin-slicing technique specifically designed to help students develop such skills. We identify a variety of sample film excerpts that illustrate several group behaviors—behaviors that recent research suggests can influence group effectiveness in different contexts. We end by discussing which group phenomena may or may not be particularly well-suited to this technique.